Biomolecule based fiber supercapacitor for implantable device. (May 2018) - Sim, Hyeon Jun; Choi, Changsoon; Lee, Dong Yeop; Kim, Hyunsoo; Yun, Ji-Hyun; Kim, Jung Min; Kang, Tong Mook; Ovalle, Raquel; Baughman, Ray H.; Kee, Chang Won; Kim, Seon Jeong
Abstract: With the growing demand for electronic medical devices for healthcare applications, we studied an implantable supercapacitor that can operate in an implantable electronic device. Here, we report a flexible implantable fiber supercapacitor for an in vivo energy storage device. The fiber supercapacitor has a high flexibility and a high potential to be applied in an implant device because the fiber can be implanted in the blood vessel and the wound can be stitched with the fiber-like suture. The fiber electrodes were fabricated in a biscrolling process that trapped poly(3, 4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS)/ferritin nanoclusters within multiwalled carbon nanotube (MWNT) sheets that provide mechanical strength and electrical conductivity. In addition, the supercapacitor is biocompatible because the MWNT sheets are coated with biocompatible materials such as PEDOT:PSS and ferritin. The areal capacitance of the PEDOT:PSS/ferritin/MWNT fiber supercapacitor was 32.9 mF/cm 2 in a phosphate buffered saline solution, and the areal energy density was 0.82 μWh/cm 2 ; these values are 52 times higher than that of the guest-free MWNT yarn. The supercapacitor operated well in a mouse and exhibited excellent biocompatibility; the capacitance was maintained above 90% in the mouse after eight days. Graphical abstract: The fiber supercapacitor has a high flexibility and a high potential to be applied in an implant device because the fiber can be implanted in the blood vessel and the wound can be stitched with the fiber-like suture. The supercapacitor operated well in a mouse and exhibited excellent biocompatibility. fx1 Highlights: Abdominal muscle of the mouse was stitched with the micro-diameter fiber supercapacitor like suture. The flexible fiber supercapacitor performance was maintained above 90% in the mouse after eight days. The PEDOT:PSS/ferritin nanocluster was enhancing the areal capacitance by the synergistic effect.